2005
DOI: 10.1111/j.1471-8286.2005.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of allowing for mismatches as a way to manage genotyping errors in parentage assignment by exclusion

Abstract: In parentage assignment by exclusion, using multiple and very polymorphic loci, genotyping errors are a major cause of non‐assignment. Using stochastic simulations, we tested the possibility to allow for mismatches at one or more allele as a way to recover assignment power. This was very efficient provided the set of loci used had a high assignment power (> 99%) and the error rate was not too high (below 3–4%). In these cases, most of the theoretical assignment power could be recovered. We also showed the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 15 publications
1
99
1
4
Order By: Relevance
“…It is also possible that some of the assigned embryos could be the product of type I error (false assignment) (Kalinowski et al, 2007;Oddou-Muratorio et al, 2003;Vandeputte et al, 2006); however, the set of embryos used for the mode of inheritance analyses were the same used in paternity analysis, thus it is unlikely that false assignment has a significant contribution. The number of unassigned embryos/female parent varied between 2 (Family 25) and 14 (Families 3, 39, and 40), this could be a function of female receptivity timing with outside pollen and/or the lack of informative nature of the embryos' genotypes (Tab.…”
Section: Paternity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that some of the assigned embryos could be the product of type I error (false assignment) (Kalinowski et al, 2007;Oddou-Muratorio et al, 2003;Vandeputte et al, 2006); however, the set of embryos used for the mode of inheritance analyses were the same used in paternity analysis, thus it is unlikely that false assignment has a significant contribution. The number of unassigned embryos/female parent varied between 2 (Family 25) and 14 (Families 3, 39, and 40), this could be a function of female receptivity timing with outside pollen and/or the lack of informative nature of the embryos' genotypes (Tab.…”
Section: Paternity Analysismentioning
confidence: 99%
“…The remaining unassigned 121 (22%) could be either the product of gene flow from the neighbouring orchard or their genotypes were not informative enough for assignment to any of the orchard's 41 parents (i.e., type II error (false exclusion) (Kalinowski et al, 2007;Oddou-Muratorio et al, 2003;Vandeputte et al, 2006)) or a combination of the two. It is also possible that some of the assigned embryos could be the product of type I error (false assignment) (Kalinowski et al, 2007;Oddou-Muratorio et al, 2003;Vandeputte et al, 2006); however, the set of embryos used for the mode of inheritance analyses were the same used in paternity analysis, thus it is unlikely that false assignment has a significant contribution.…”
Section: Paternity Analysismentioning
confidence: 99%
“…Nestlings with a positive trio LOD score that mismatched their social father's genotype at maximally one locus were classified as WPO. Mismatches at only one locus are most likely due to null alleles, mutations, spurious alleles or genotyping errors [42,43]. We determined the paternity status (WPO or EPO) of 464 offspring originating from 157 broods.…”
Section: Methodsmentioning
confidence: 99%
“…(Cercueil et al 2002) No S. trutta application found but see Vandeputte et al 2006PEDAGREE (Coombs et al 2010 No S. trutta application found but see EasyPOP (Balloux 2001) No S. trutta application found but see Castric et al 2002;Gomez-Uchida et al 2008;Whiteley et al 2010FPG (Hey 2004 No salmonid application found SFS-CODE (Hernandez 2008) No salmonid application found Coalescent simulation models MS (Hudson 2002) No salmonid application found SEQ-GEN (Rambaut & Grassly 1997) Cortey et al 2009 SIMCOAL (Excoffier et al 2000;Laval & Excoffier 2004) No salmonid application found DIY ABC (Cornuet et al 2008) No S. trutta application found but see Nikolic et al 2009 Quantitative genetics: animal model MCMCglmm R package (Hadfield 2010) Serbezov et al 2010bVCE (Groeneveld 1994 No S. trutta application found but see Martyniuk et al 2003;Wilson & Rannala 2003;Norris 2004;Perry et al 2004, 2005 DFREML (replaced by WOMBAT) (Meyer 1988(Meyer , 2007 No S. trutta application found but see Hard et al 1999;Rogers et al 2002;Garant et al 2003;Araneda et al 2005;Paez et al 2010 (Ortigosa et al 2000) No salmonid application found HABSCORE (Milner et al 1993) Barnard et al 1995 Habitat-hydraulic models e.g., 'What are the habitat preferences of a fish population in relation to stream discharge?' (Parasiewicz 2001(Parasiewicz , 2007 No salmonid application found EVHA (Ginot 1995;P...…”
Section: Population Dynamics Modelsmentioning
confidence: 99%